Analisis Keterkaitan Penyakit Pasien pada Puskesmas Menggunakan Metode Association Rule - karina auliasari; Yuli Susanti (Faculty of Computer Science, University of Jember, 2016)
The need for vigilance against the disease is an effort to reduce morbidity and prevalence of complications in diseases. Medical records of hospitalized patients in the many and varied Puskesmas can then be processed to analyze the pattern of disease that often affects people in the area around Puskesmas. Implementation of association rule method is expected to generate linkages between the rule of item combinations of diseaseThe data used in this research is an inpatient medical records of patients Brang Rea Puskesmas from January to June 2015. The system was developed using the programming language Visual Basic and Microsoft SQL Server 2008 as the database. Tests on the analysis modules generate output system of rules